Impact of physical layer impairments on SDM networks based on ROADM nodes - Silva, Marco Quiteres da (2022)
Current transport optical networks are approaching its capacity limits, mainly due to new applications and services that require a huge amount of resources. To increase the network capacity, multiband solutions, that exploit the unused capacity of actual fibers, in particular the L-band, are being currently commercially explored. However, this strategy is assumed as a short to medium term solution. A long-term solution is to use spatial-division multiplexing (SDM) in the optical domain, which leads to the concept of SDM-based optical networks. In this work, different SDM switching architectures (spatial, spatial-wavelength, wavelength, fractional space-full wavelength) are studied and compared in terms of cost per bit, power consumption and flexibility. For the switching architectures with spatial and spatial-wavelength granularities (the architectures that have superior performance), the most relevant physical impairments (PLIs) (amplifiers noise, non-linear interference, narrowing penalty due to filtering and in-band crosstalk) are analytically studied, for a SDM reconfigurable optical add-drop multiplexer (ROADM) cascade. Furthermore, a Monte Carlo simulation is used to assess more rigorously the PLIs effects on the performance of SDM ROADMs, with spatial-wavelength switching architecture, in cascade. The main difference, regarding PLIs, between the single spatial channel ROADM architecture and the SDM ROADM architectures is the enhanced effect of in-band crosstalk. For cascaded ROADMs with 16 directions, 19 spatial channels and filtering isolation of -25 dB, the in-band crosstalk can lead to a 2 dB optical signal-to-noise ratio penalty. Due to this penalty, the signal crosses less 9 ROADMs than in a single spatial channel ROADM architecture.